Mineralogical and experimental study of serpentine minerals and ultramafic rocks with application to carbon capture and storage by mineralisation - Lacinska, Alicja M. (2016)
The type of feedstock and host rock utilised in ex situ and in situ Carbon Capture and Storage by Mineralisation (CCSM) is an important aspect of these technologies, and detailed appraisal of candidate mineral/rock performance in the presence of CO2 may greatly improve CCSM efficiency. Here, a detailed mineralogical and geochemical investigation of serpentine minerals and ultramafic rocks under laboratory-controlled experiments simulating ex situ and in situ process conditions is presented. Feedstock serpentine minerals were analysed comprehensively, prior to experimental processing. The identification of antigorite was unequivocal using a combination of X-ray diffraction, Fourier Transform Infrared Spectroscopy and/or Thermo-gravimetric Analysis. However, the analysis of chrysotile and lizardite proved to be more challenging, especially when the two polymorphs were finely inter-grown. This study highlighted the structural, textural and chemical complexity of serpentines and showed that great care must be taken when analysing this mineral group for CCSM. Investigation of the acid leaching of serpentine minerals under conditions of 70°C and 1.4M NH4HSO4 provided fundamental insights into the rate and extraction efficiency (EE) of Mg2+ and associated controlling factors, under conditions relevant for ex situ CCSM. It is demonstrated that EE is a function of mineral reactivity and depend on a complex interplay between crystal structure and chemistry. Generally, poorly crystalline and highly disordered phases with low levels of Al3+ were found to be suitable feedstock materials for acid digestion pre-treatment. Chrysotile, lizardite 2H1 and poorly crystalline serpentines showed up to 85% Mg2+ EE after 3 h of acid leaching, and hence are recommended as best feedstock materials for CCSM, whilst antigorite and Al3+-rich serpentines proved to be largely unsuitable, showing low levels of EE of ~ 20%. Examination of dunite, harzburgite and serpentinite under conditions relevant for in situ CCSM, i.e. 70°C and 100 bar CO2 pressure, provided insights into rock reactivity as a function of composition and texture, and the progression of in situ mineral carbonation. The rate of net Mg release and thus the extent of subsequent carbonation were greatest for serpentinite, providing ca. 3% carbonation after six months. However, mineral reactivity within serpentinite was preferential, i.e. significantly enhanced within secondary vein serpentine, being thus, the main source of Mg2+ for magnesite precipitation. Reaction-induced transformation and hence mineral carbonation of dunite and harzburgite were less pronounced over the same time-scale. The reaction of serpentinite with wet supercritical CO2, as opposed to CO2-saturated brine, significantly affected rock integrity, with the exposure of more surface area and promotion of fluid-rock interaction. In particular, it is shown that ferric iron oxidation and the precipitation of goethite impacts upon surface mineral dissolution at exposed surfaces, thereby hindering subsequent carbonation. Overall, this study highlighted the importance of host rock choice for in situ CCSM and the need for detailed petrographical and geochemical investigation of any proposed CCSM repository prior to technological process modelling.